Proposed upgrading of Volkswagen showroom for Wearns Automotive Sdn Bhd at 204, Jalan Ampang, 50450 Kuala Lumpur, Kuala Lumpur / Muhammad Khairul Asyraf Mohd Asri - Mohd Asri, Muhammad Khairul Asyraf (Faculty of Architecture, Planning and Surveying, 2010)
This is the last project for student Diploma in Interior Architecture. The plan is a powerful tools in the design process that requires both intellectual and creative rigor. The focus of this article is the methodology of hoe the plan is presented, developed and understood in sophomore interior architecture studio. The studio’s goal is to give students a foundation of understanding by broadening their knowledge of spatial design through the study of the plan and plan language. The plan is what architects, interior designers and landscape designers use to move people through space, to organize space, and to place objects in space. The proposed design upgrading for the new interior WEARNS AUTOMOTIVE Sdn Bhd, is located at 204, Jalan Ampang, 50450 Kuala Lumpur, Malaysia. The project was proposed because VOLKSWAGEN has issued instructions to all the subsidiaries to convert a new concept. With the creation of this exhibition room, it can attract more people visiting the exhibition room is about novelty and taste Volkswagen.